Analisis Gaya Belajar Visual, Audiotori dan Kinestetik dalam Pengembangan Prestasi Belajar Siswa - Susi Lestari; Muhammad Widda Djuhan (Institut Agama Islam Negeri Ponorogo, 2021)
This research is motivated by the learning achievement in social studies subjects at SMPN 1 Purwantoro which can be categorized as less, compared to other subjects. This is because the learning process in the classroom does not make students interested in the teaching style applied by the teacher. This study aims: To determine the form of visual, audiotory and kinesthetic learning styles of students in developing student achievement in social studies subjects. The design in this study the researcher used a qualitative approach with data collection methods in the form of interviews, observation and documentation. This research was conducted at SMPN 1 Purwantoro with 32 students as the subject of research in class VIII E. The results of the research in the formulation of the first problem, namely the form of visual learning styles in the development of learning achievement in social studies subjects at SMP 1 Purwantoro with the material of economic actors include: (1) learning using a blackboard and LCD, (2) learning by summarizing the material, (3) ) learn by watching videos. The results of the research in the formulation of the second problem were the form of students' audiotory learning styles in the development of social studies subjects at SMPN 1 Purwantoro, namely: (1) learning by discussion, (2) learning while listening to music. The results of the third study, namely the form of student learning styles that have kinesthetic learning styles are: (1) learning by using body language (2) reading while walking. The results of the research in the formulation of the fourth problem, namely the results of the visual, audiotory and kinesthetic learning styles of each student have a good value on the learning styles that each student tends to have.